Stereoselective β‐Mannosylation by Neighboring‐Group Participation. (12th July 2016) - Elferink, Hidde; Mensink, Rens A.; White, Paul B.; Boltje, Thomas J.
Abstract: The stereoselective synthesis of glycosidic bonds is the main challenge of oligosaccharide synthesis. Neighboring‐group participation (NGP) of C2 acyl substituents can be used to provide 1, 2‐ trans ‐glycosides. Recently, the application of NGP has been extended to the preparation of 1, 2‐ cis ‐glycosides with the advent of C2 chiral auxiliaries. However, this methodology has been strictly limited to the synthesis of 1, 2‐ cis ‐gluco‐type sugars. Reported herein is the design and synthesis of novel mannosyl donors which provide 1, 2‐ cis ‐mannosides by NGP of thioether auxiliaries. A key element in the design is the use of 1 C4 locked mannuronic acid lactones to enable NGP of the C2 auxiliary. In addition to C2 participation a new mode of remote participation of the C4 benzyl group was identified and provides 1, 2‐ cis ‐mannosides.